(3MhGTj EHf GdJdejP Ydi GdeGFI GdeSjMjIs - (3Cejf GdOhdI gHI Gddg Hf UGYO Hf EHQGgje Hf GdJdejPs; (3YjSi Hf jMji GdeSjMj GdLQLGfj, CHh Sgd,J (B401 (3g` s ((3gHI Gddg Hf edcG GdeJWjH GdfUQGfi GdJcQjJj s)
(3ChdgG (B:s
(3HSe Gddg GdQMef GdQMjegPg GdMhGTi dCejf GdOhdI bGd CHh Sgd YjSi Hf jMji GdeSjMi ai GdcJGH GdKGdK ef GdeGFI (B: (3GdYXGe eGFJGf hSJI hCQHYhf YXekG, hPdc Shi GdPi ai GdMfLQI hGdPi ai GdbdH s
(3BNQgG (B:s
(3Pdc dJbhjI GdCOhjI GdePchQI, GdMGQ GdZQjRi , heYhfJg HbhGgG Ydi JMdjd GdSeheGJ MGQgG hHGQOgG, hdaYdgG fMh CUdgG CjVkG s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH GdKGfis
(3GfXQ GjVG GdeGFI GdeSjMjIs
(3fSNI eLdS ThQGi Qbe(B"705"s
(3bQf GdfSN (B:s
(3GdbQf GdSGHYs
(3JHUQI GdYfhGf (B:s
(3JPjjds
Keywords: (3GdWHs